2012
DOI: 10.1073/pnas.1204523109
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxin resistance via reversible methylation of the DPH4 promoter is a unique survival strategy

Abstract: HA22 is a recombinant immunotoxin composed of an anti-CD22 Fv fused to a portion of Pseudomonas exotoxin A. HA22 produced a high rate of complete remissions in drug-resistant hairy cell leukemia and has a lower response rate in pediatric acute lymphoblastic leukemia (ALL). To understand why patients with ALL have poorer responses, we isolated an ALL cell line that is resistant to killing by HA22. The resistance is unstable; without HA22 the cells revert to HA22 sensitivity in 4 mo. We showed that in the resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 44 publications
1
56
0
Order By: Relevance
“…10 Notably, intermittent exposure to sublethal doses of moxetumomab pasudotox in vitro can lead to reversible epigenetic changes that confer resistance in ALL cell lines. 24,25 This potential mechanism of resistance has not yet been explored in patients. Finally, we recently demonstrated wide interpatient variability in the exposure time required to induce cytotoxicity of ALL blasts by moxetumomab pasudotox.…”
Section: Discussionmentioning
confidence: 99%
“…10 Notably, intermittent exposure to sublethal doses of moxetumomab pasudotox in vitro can lead to reversible epigenetic changes that confer resistance in ALL cell lines. 24,25 This potential mechanism of resistance has not yet been explored in patients. Finally, we recently demonstrated wide interpatient variability in the exposure time required to induce cytotoxicity of ALL blasts by moxetumomab pasudotox.…”
Section: Discussionmentioning
confidence: 99%
“…However, some patients do not respond, whereas others relapse after initially responding to the agent. We have undertaken studies to understand possible mechanisms that can lead to resistance and recently reported that silencing of the DPH4 gene in the HAL-01 ALL cell line results in immunotoxin resistance (13). Here, we have selected CA46 cells, which are immunotoxin-resistant, and observed that the resistant cells have a deletion of the WDR85 gene, which causes a novel modification of diphthamide in EF2 and immunotoxin resistance.…”
Section: Acute Lymphoblastic Leukemia (All)mentioning
confidence: 99%
“…We have recently reported that immunotoxin resistance in the HAL-01 ALL cell line is mediated by reversible DNA methylation in the CpG island of the DPH4 promoter region (13). To study the WDR85 promoter in CA46-R cells, we attempted to amplify the promoter region (spanning Ϫ1588 to ϩ17 bp) by PCR using three primer pairs and were unable to do so, suggesting that the region was deleted in the resistant cell line.…”
Section: Reduced Wdr85 Expression In the Ca46-r Cell Line Is Responsimentioning
confidence: 99%
“…Although these new recombinant immunotoxins have shown high potency in killing tumour cells with high specificity, they too share the limitation of targeting a single cellular substrate, eEF-2 (Jørgensen et al, 2008). In fact, mutations in eEF-2 have been shown to emerge easily, conferring resistance to these toxins in cancer cells (Foley et al, 1995;Jørgensen et al, 2008;Wei et al, 2012). & Barbieri, 2003;Garrity-Ryan et al, 2004), which play important roles in survival, proliferation, metastasis and angiogenesis in cancer.…”
Section: Introductionmentioning
confidence: 99%